Lectotypification of Callicarpa nudiflora (Lamiaceae) - Ma, Zhonghui; Su, Zhiwei (Phytotaxa, 2015)
Callicarpa nudiflora Hooker & Arnott (1837: 206) was formally described in 1837 from plants collected in China. In the protologue, two collections (Mr. Millett s.n and Rev. G. H. Vachell 263) were cited, but no type was indicated.We traced in E three specimens that fit the protologue and can be regarded as syntypes (Art. 9.5 of the ICN, McNeill et al. 2012): two duplicates specimens labelled “Rev. G. H. Vachell 263” (E barcodes E00369187, E00369189) and one specimen “Millet s.n.”. The specimen “Rev. G. H. Vachell 263” with barcode E00369187 is better preserved and more complete than the other two specimens, with obvious gray elliptic lenticels on the branchlets which is one of the crucial identification characters for this species and, hence is here designated as the lectotype.